Effect of Work Motivation and Training on Employee Performance of PT. Deltavista Nusantara – Jakarta Selatan - Sri Sukartono (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of Work Motivation (X1), Job Training (X2), on Employee Performance (Y) PT. Deltavista Nusantara - South Jakarta. The research method used is a questionnaire distributed via Google Form at PT. Deltavista Nusantara - South Jakarta. By using quantitative research. The data analysis method used is multiple linear regression analysis by testing the hypothesis, namely the t test and F test with the help of the SPSS 22 program. The sample in this study was 133 employees who were selected using the slovin formula. The variables used in this study are Work Motivation (X1), Job Training (X2), as the independent variable and Employee Performance (Y) as the dependent variable. The results of this study indicate that work motivation has no significant effect on employee performance at PT. Deltavista Nusantara – South Jakarta. Job Training has a significant effect on Employee Performance of PT. Deltavista Nusantara – South Jakarta. Then work motivation and job training simultaneously have a significant effect on employee performance at PT. Deltavista Nusantara – South Jakarta and the coefficient of determination (R Square) is 0.294, which means that 29.4% of employee performance is influenced by work motivation, job training and the remaining 70.6% is explained by other variables outside of this study.